2017
DOI: 10.1186/s12870-017-1102-7
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of chromosome condensation in plants with large chromosomes

Abstract: BackgroundMost data concerning chromosome organization have been acquired from studies of a small number of model organisms, the majority of which are mammals. In plants with large genomes, the chromosomes are significantly larger than the animal chromosomes that have been studied to date, and it is possible that chromosome condensation in such plants was modified during evolution. Here, we analyzed chromosome condensation and decondensation processes in order to find structural mechanisms that allowed for an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 41 publications
4
12
0
Order By: Relevance
“…The diploid species, N. sativa, N. damascena, N. arvensis, N. hispanica and N. orientalis (2 n = 2 x = 12), have five metacentric and one telocentric chromosome pairs, but N. bucharica and N. integrifolia (2 n = 2 x = 14) have four metacentric, two submetacentric and one subtelocentric chromosome pairs ( Gilot-Delhalle et al, 1976 ). The 1C-values of N. sativa and N. damascena were determined to be 10.39 Gbp ( Bennett and Smith, 1976 ) and 10.29 Gbp ( Evans et al, 1972 ; Kuznetsova et al, 2017 ; Leitch et al, 2019 ), respectively. There is little information about the genome composition and cytogenetic characteristics of Nigella species although such information is important to understand the phylogenetic relationship in this genus.…”
Section: Introductionmentioning
confidence: 99%
“…The diploid species, N. sativa, N. damascena, N. arvensis, N. hispanica and N. orientalis (2 n = 2 x = 12), have five metacentric and one telocentric chromosome pairs, but N. bucharica and N. integrifolia (2 n = 2 x = 14) have four metacentric, two submetacentric and one subtelocentric chromosome pairs ( Gilot-Delhalle et al, 1976 ). The 1C-values of N. sativa and N. damascena were determined to be 10.39 Gbp ( Bennett and Smith, 1976 ) and 10.29 Gbp ( Evans et al, 1972 ; Kuznetsova et al, 2017 ; Leitch et al, 2019 ), respectively. There is little information about the genome composition and cytogenetic characteristics of Nigella species although such information is important to understand the phylogenetic relationship in this genus.…”
Section: Introductionmentioning
confidence: 99%
“…1, 3) and the longest chromosome length (Table 1) in comparison with the other three species. It is suggested that genome sizes of the plants are strongly correlated with chromosome length mainly due to the amount of repetitive DNA sequences in Lilium (Du et al 2017) and Nigella damascena (Kuznetsova et al 2017). Therefore, the present results suggest that the abundance of repetitive DNA in the genomes might have contributed to the genome sizes in Lactuca species, and it is reflected as the CPs of the chromosomes.…”
Section: Discussionmentioning
confidence: 55%
“…This is because the limit of the cell dimension and spindle extension do not favour chromosomes with significantly different lengths, which in turn decreases evolutionary fitness [ 31 ]. Chromosomes of various lengths may also differ in chromosome condensation [ 32 , 33 ], affecting chromosome stiffness and sister chromatid division during mitosis [ 34 ]. The decrease in chromosome velocity (movement) was shown to be reduced by specific chromosome positioning so far in Melanoplus [ 35 ].…”
Section: Introductionmentioning
confidence: 99%